2003
DOI: 10.1111/j.1559-1816.2003.tb01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Racism or Sexism? Attributional Ambiguity and Simultaneous Membership in Multiple Oppressed Groups1

Abstract: This study examines short‐term psychological effects of prejudice attributions on African American women. Black female college students (N= 112) imagined themselves in an audiotaped scenario in which White male students made negative evaluations of them. Participants completed self‐report measures of psychological stress and state self‐esteem after they rated the likely contributions of various causal attributions to the negative evaluations. Attributions included personal characteristics of the participant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 62 publications
5
55
1
2
Order By: Relevance
“…In a sample of African American female college students, King (2003) found that racism and the interaction of racism and sexism predicted increased stress. However, Szymanski and Stewart (2010) found that when examining internalized racism and sexism concomitantly in a sample of adult African American women, only sexism emerged as a significant predictor of distress.…”
Section: Racism and Sexism As Stressorsmentioning
confidence: 97%
“…In a sample of African American female college students, King (2003) found that racism and the interaction of racism and sexism predicted increased stress. However, Szymanski and Stewart (2010) found that when examining internalized racism and sexism concomitantly in a sample of adult African American women, only sexism emerged as a significant predictor of distress.…”
Section: Racism and Sexism As Stressorsmentioning
confidence: 97%
“…The intersection of these specific race, gender, class, or age statuses confers health risks for African American women that are currently not fully included in empirical research. 6,11,21,28 Examination of intersectionality is also important because this approach frames health disparities not as characterizations of groups historically known to be disadvantaged, such as African Americans, the poor, women, or the elderly, but as a consequence of long-standing social, economic, and political processes that create hierarchies of privilege, power, and opportunity. The intersectional approach provokes examination of the ways in which race, gender, class, and age are not discrete or additive but, instead, are multiplicative, interlocking, interactive, and relational in how they structure vulnerability.…”
Section: Intersectionality Researchmentioning
confidence: 99%
“…[11][12][13] African American women occupy subordinate and disempowered positions in the social hierarchies of race and gender and can experience "gendered racism," which describes how racism and sexism intertwine to subject African American women to a unique form of oppression that disparages being female and black simultaneously. 28 Differentiating sexism from racism is difficult.…”
Section: Intersectionality Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown y Hewstone (2005) encuentran correlación entre el prejuicio étnico y racial con actitudes negativas hacia otras minorías. Así, las personas que manifiestan prejuicio contra minorías étnicas suelen obtener correlaciones altas con otras medidas de prejuicio general (Dunbar, 1995), sexismo (Glick y Fiske, 1995;King, 2003), prejuicio hacia las mujeres (Fiske y Von Herdy, 1992;Swim, Aikin, Hall y Hunter, 1995), hacia las personas homosexuales (Cárdenas, 2007) o referidas a antisemitismo (Dumbar, 1995;Dunbar y Simonova, 2003). Además, estas personas suelen mantener escaso contacto y bajos niveles de intimidad con las personas pertenecientes a los exogrupos.…”
Section: Medida De Las Actitudes Y Prejuiciosunclassified